CARDIOPROTECTIVE EFFECT OF TUMOR NECROSIS FACTOR ALPHA ANTAGONIST IN DOXORUBICIN MYOCARD TOXICITY - M. I. Popovich; L. M. Cheban; L. A. Taku; V. М. Ivanov; I. М. Popovich; M. V. Ivanov; V. А. Rotaru; L. S. Mikhalchan; V. A. Kobets (Кардиоваскулярная терапия и профилактика)
Doxorubicin (Dox) is a first line drug in neoplasia treatment. It is however cardiotoxic even in moderate dosages. High mortality of oncological patients from cardiomyopathic heart failure on Dox treament is a serious problem of oncology and cardiology. Among the cardiotoxicity factors of Dox are activation of inflammatory reaction and ability of the drug to increase expression of tumor necrosis factor alpha (TNF-a) in myocardium and coronary arteries.Aim. To study in laboratory conditions the opportunities for cardioprotection from Dox with TNF-a antagonist.Material and methods. Doxorubicin myocardial damage (DMD) was simulated on the white rats by intraabdominal load of Dox in cumulative dosage 16 mg/kg within 2 weeks. In other series, to the animals together with Dox every day during 2 weeks intraabdominally the TNF-a antagonist was loaded — monoclonal antibody (ma-TNF-a) dosage 5,0 mg/kg. Cardioprotective effect ma-TNF-a was evaluated on the perfusion model of the isolated heart with assessment of: (1) inotropic response of myocardium on stimulation by noradrenalin and endothelin-1 (ET-1); (2) coronary functional reserve on acetylcholine, adenosine, bradikinine and hydrogen peroxide influence; (3) dynamics of end diastolic pressure (EDP) of the left ventricle in the ischemia-reperfusion syndrome.Results. In DMD, there was significant disorder of the diastole, systole and pumping function of the heart even in physiological values of filling and resistance. Action ma-TNF-a was followed by a significant increase of cardiac output, maximum velocity of isovolumetric contraction and relaxation by 14,2-26,3%, and significant decrease of EDP by 30,1%. With action of ET-1 on the heart with DMD there was negative inotropic effect, mediated by the decrease of systolic pressure (SP) in LV by 9,1% comparing to the baseline, and when ma-TNF-a made analogically to control positive inotropic effect (SP in LV increased by 8,5%) and increase of cardiac output by 14,3%. Cardioprotective effect of ma-TNFa followed by significant increase of coronary functional reserve. It is notable that coronary reactivity, common for the action hydrogen peroxide and mediated by hyperpolarization, did not change in DMD. Usage of ma-TNF-a improved resistance of the heart to ischemia and reperfusion, as the measured EDP values measured at various time frames were significantly lower than EDP, and the level of SP in LV — significantly higher.Conclusion. Usage of TNF-a antagonist in DMD made cardioprotective effect: significant increase of cardiac output, SP, maximum velocity of isovolumetric contraction and relaxation, significant decrease of EDP, appearance of postitive inotropic response of the heart on ET-1, and improvement of endothelium-dependent coronary dilation. Action of ma-TNF-a was followed by decrease of ischemic cardiac contracture and significantly better recovery of SP and EDP during reperfusion.